Analysis and Development of A Web-Based Digital Pawn Application and Application Management Information System to Improve Transparency and Efficiency of Collateral Services - Rayhan Malona Clemens Latuconsina; Mario Iskandar (CV. Green Publisher Indonesia, 2026)
Pawn services represent one of the fastest financial solutions for lower-middle-income communities. However, manual and non-transparent appraisal processes often create uncertainty for prospective customers regarding the valuation of pledged assets. This study aimed to design and develop a digital pawn information system that emphasized automated price appraisal features and online pawn applications. The system integrated an artificial intelligence (AI)-based automated appraisal engine with a human-in-the-loop approach, in which the system generated objective appraisal recommendations that were subsequently validated by administrators to ensure decision accuracy and accountability. The transparency indicator in this system was implemented by providing customers with a real-time estimated loan value range (minimum and maximum limits) based on measurable asset specifications, thereby reducing subjectivity during the initial assessment process. Key system features included a pawn value estimation calculator, a physical item photo documentation upload form to support remote verification, and a centralized management dashboard for application validation. The research findings are expected to reduce service waiting times compared with conventional methods and provide customers with greater certainty regarding estimated appraisal values before completing physical transactions.